Resilience building Initiatives to Counter Shocks and Stressors Affecting Rural Communities in Chiredzi District, Zimbabwe - Rameck Defe; Mark Matsa (Springer, Cham, 2022)
Zimbabwe has experienced innumerable shocks and stressors which are bedeviling economic and social development. Shocks in the form of natural hazards (droughts, floods), epidemics, environmental degradation, and cash crisis severity, scope and impact have necessitated coalition of stakeholders and development of resilience building initiatives to counter shocks and stressors in a manner that protects livelihoods and recovery gains. This study sought to assess the effectiveness of implemented resilience building initiatives to counter shocks affecting rural communities of Chiredzi District, Zimbabwe. Initiatives were implemented through the Enhanced Community Resilience and Sustainability (ECRAS) projects led by Care International and Plan International targeting to increase the capacities of Chiredzi District communities to withstand shocks and stressors. Questionnaires, interviews, and direct field observations were used to gather field data. Questionnaires were electronically administered using kobo collect to respondents randomly selected from conveniently sampled wards involved in resilience building initiatives in Chiredzi District. Interviews were conducted with purposively sampled key informants who included District Agritex officer, District Administrator, District Social Services, Care International Monitoring and Evaluation Officer, Plan Project facilitator and Ward Councilors. Findings revealed three main categories of resilience building initiatives in the rural communities of Chiredzi District, namely: crop production related initiatives; livestock production related initiatives; and social and well-being related initiatives. Resilience building initiatives are effective tools to deal with recurrent shocks and stressors in rural communities of Chiredzi District which are being projected to continue for the next decades.